2016
DOI: 10.1136/lupus-2016-000163
|View full text |Cite
|
Sign up to set email alerts
|

Off-label use of rituximab for systemic lupus erythematosus in Europe

Abstract: ObjectivesRituximab (RTX) is a biological treatment used off-label in patients with systemic lupus erythematosus (SLE). This survey aimed to investigate the off-label use of RTX in Europe and compare the characteristics of patients receiving RTX with those receiving conventional therapy.MethodsData on patients with SLE receiving RTX were taken from the International Registry for Biologics in SLE retrospective registry and complemented with data on patients with SLE treated with conventional therapy. For nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 38 publications
1
37
0
4
Order By: Relevance
“…Data from Ryden-Aulin et al study about the off-label use of RTX for SLE in Europe showed that RTX is used in 4% to 20% of SLE patients in Sweden, up to 11% in Spain, and 7% in the U.K. Moreover, adoption of RTX for management of SLE ranged from 1% to 4% in other European countries (58). The off-label use of RTX in SLE is enabled by its favorable safety profile and the documented benefit that led to its approval by the FDA and the European Medicines Agency for the treatment of rheumatoid arthritis and ANCA-associated vasculitis (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Data from Ryden-Aulin et al study about the off-label use of RTX for SLE in Europe showed that RTX is used in 4% to 20% of SLE patients in Sweden, up to 11% in Spain, and 7% in the U.K. Moreover, adoption of RTX for management of SLE ranged from 1% to 4% in other European countries (58). The off-label use of RTX in SLE is enabled by its favorable safety profile and the documented benefit that led to its approval by the FDA and the European Medicines Agency for the treatment of rheumatoid arthritis and ANCA-associated vasculitis (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab (MabThera ® /Rituxan ® ), a chimeric monoclonal antibody that targets and depletes CD20‐positive B cells, has a safety profile that is well characterized and established in the approved oncology indications (non‐Hodgkin's lymphoma, chronic lymphocytic leukemia) and autoimmune indications (rheumatoid arthritis [RA], granulomatosis with polyangiitis [GPA] and microscopic polyangiitis [MPA], and pemphigus vulgaris [newly approved]) . Due to its mechanism of action, rituximab is also used off label by healthcare providers (HCPs) to treat other autoimmune conditions, often in patients who are refractory to approved treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Percentage of patients with systemic lupus erythematosus receiving rituximab in 12 European countries 1 .…”
Section: Figurementioning
confidence: 99%
“…The ongoing search for effective therapies for systemic lupus erythematosus (SLE) is illustrated by a recent study by Ryden-Aulin et al 1 investigating the off-label use of rituximab for SLE in Europe. Effective, safe and affordable treatments are urgently needed for SLE.…”
mentioning
confidence: 99%
See 1 more Smart Citation